Die Schlaraffenlandkarte um 1700 - Weder, Christine (online, 2021)
Fascinating and enigmatic to this day: The Accurata Utopiae Tabula, an anonymous map of Cockaigne accompanied by an explanatory book (thought to be by Schnebelin), inspired the likes of Leibniz and was a popular supplement to atlases around 1700. Extensively embellished with euonyms for its locations, this multimedia ensemble offers a luxurious landscape of vices in addition to its ‘merry discourse of gluttony and boozing’. The multilingual map contains hidden connections to not only fictional worlds, such as the lands of giants in Rabelais and Fischart, but also to such historical realities as the early modern economy of credit. An enjoyable journey of discovery across the borders of different arts and disciplines, guided by the compass of media history. Faszinierend rätselhaft bis heute: Die Accurata Utopiae Tabula, eine anonyme Karte des Schlaraffenlandes samt Erklaerung in Buchform, vielleicht von einem gewissen Schnebelin, hat schon Leibniz bestrickt und war um 1700 als Beigabe zu Atlanten beliebt. Akribisch ausstaffiert mit sprechenden Ortsnamen, bietet das multimediale Ensemble nebst »lustigem Freß- oder Sauff-Discurs« eine luxuriöse Landschaft der Laster. Die mehrsprachige Wortschatzkarte unterhält versteckte Verbindungen zu fiktiven Welten wie dem Riesenreich Rabelais’ bzw. Fischarts, aber auch zu Wirklichkeiten wie der frühneuzeitlichen Ökonomie des Kredits. Eine vergnügliche Entdeckungsreise mit mediengeschichtlichem Kompass über die Grenzen der Künste und Disziplinen hinweg.
Keywords: Accurata Utopiae Tabula; Karneval; Landschaft der Laster; Mediengeschichte; Michail Bachtin; Schlaraffia; Utopie; Wortschatzkarte; Geschichtklitterung; Johann Fischart; Gargantua; François Rabelais; François Fénelon; Johann Andreas Schnebelin; Johann Baptist Homann; 18. Jahrhundert; 17. Jahrhundert; Frühe Neuzeit; Theologie; Laster; Ökonomie; Schulden; Kerbholz; Kredit; Geld; Überfluss; Luxus; Atlas; Kartographie; Topologie; Topographie; Raumlogik; Raumdarstellung; Grenze; intermedial; imaginär; Landkarte; Karnevalisierung; Fiktion; Literatur; Schlaraffenland; CF; HB; 2AD; 3JD; JFC; JFD; HBTB; 2ACG